IMMUNE TOLERANCE INDUCED BY GAMMA－RAY IRRADIATION - 练燕 王延江 粟永萍 冉新泽 艾国平 刘晓宏 郭朝华 程天民 (Chinese journal of cancer research, 2003)
Objective: To detect the existence of immune tolerance induced by gamma-ray irradiation. Methods:Peritoneal cells were harvested from mice subjected to 5 Gy ^60Co gamma-ray total body irradiation at 3d, 7d, 15d and 30d, then their counts, morphological changes and IL-12 gene expression were investigated. Results: After irradiation, the peritoneal cells were sharply reduced,the cell morphology shifted from round-like to polymorphic and fusiform with some processes,expression of IL-12 p35 was seriously suppressed, while that of IL-12 p40 greatly enhanced. Conclusion: Our data highly suggest that the gamma-ray irradiation could potentially induce dendritic cell (DC) commitment and immune tolerance.